In like a lion, out like a lamb - Bauer, Marion Dane; McCully, Emily Arnold (New York : Holiday House, 2011)
Describes in verse the lion that is March weather, which finally gives way to the lamb of spring
004-008
Keywords: March (Month) -- Juvenile fiction; Spring -- Juvenile fiction; Stories in rhyme; March (Month) -- Fiction; Spring -- Fiction